2022
DOI: 10.1186/s12910-022-00878-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and values among the Swedish general public to using human embryonic stem cells for medical treatment

Abstract: Background The use of human embryonic stem cells (ES cells) for the development of medical therapies is surrounded with moral concerns. The aim of this study was to assess the public’s attitudes toward the use of ES cells for treatment of Parkinson’s disease (PD) and other diseases, what factors are most important to consider when using ES cells for drug development, and if there is an association between religious beliefs and attitudes toward using ES cells for medical treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The higher the score, the stronger the individual's perception of social support). ( 3) Individual characteristics used as control variables include gender, age, ethnicity, political affiliation, and health literacy [13]. (The individual's ability to obtain and understand health information to ensure and promote their own health.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The higher the score, the stronger the individual's perception of social support). ( 3) Individual characteristics used as control variables include gender, age, ethnicity, political affiliation, and health literacy [13]. (The individual's ability to obtain and understand health information to ensure and promote their own health.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Currently, there are multiple methods for obtaining ESCs, such as activating unfertilized oocytes to develop into parthenogenetic embryos, injecting sperm into enucleated oocytes to generate androgenetic embryos, and transferring somatic cell nuclei into enucleated oocytes to induce reprogramming and establish ESC lines ( Leeb and Wutz, 2011 ; Elling et al, 2019 ). A Swedish survey reported that over half of the population had a positive attitude toward using ESCs in PD drug development ( Grauman et al, 2022 ). Studies have shown that early ESCs can differentiate into DA neurons and improve behavior when transplanted directly into the brains of rodents ( Kim et al, 2002 ; Ben-Hur et al, 2004 ), but there is a risk of teratoma formation due to the presence of undifferentiated neural epithelial cells among the transplanted cells ( Roy et al, 2006 ); therefore, complete induction of ESC differentiation is needed before transplantation.…”
Section: Stem Cell Transplantation For Pdmentioning
confidence: 99%